Musta mere ranniku eesti asunikud malaaria meelevallas - Aivar Jürgenson (Mäetagused, 2023)
At the end of the 19th century, Estonian settlers encountered malaria in the Volga region and Siberia, but outbreaks with the most serious consequences hit Estonians in the Black Sea coastal region of the Caucasus. The article looks at the first contact of the local Estonians with malaria, how the disease affected migrations and settlement activities, what the Estonians’ descriptions of the disease were, what the causes of the disease were believed to be, how malaria was treated, and what preventive measures were used against the disease. Although malaria had also been present in many parts of Europe in earlier centuries, it had almost disappeared in the second half of the 19th century due to improved hygiene and sanitation. Europeans encountered malaria mainly in colonial countries, and so did Estonians. While in Estonia there were still several outbreaks of malaria in the first half of the 19th century, it was no longer a problem in the second half of the century. Now, Estonians came into contact with malaria mainly abroad – in warmer and wetter regions, where Estonian men had been conscripted into military service (e.g., the Russo-Turkish War, the Crimean War; cf. the Turkish disease) or where they had emigrated and established settlements. The resettling of Estonians to the Caucasus, which took place in the last quarter of the 19th century, cannot be described without mentioning malaria. Malaria hit Estonians primarily in settlements built in coastal areas, where there were sufficiently moist conditions for the development of malaria mosquitoes. Estonian colonists fell very ill in the first years of settlement, and their mortality rates were high. Many Estonians decided to return to their homeland due to malaria. The struggle of the Estonian settlers of the Black Sea coast of the Caucasus with malaria occurred at a time when science had not yet discovered either the plasmodium that causes malaria or the role of mosquitoes in the transmission of the disease. The colonial authorities had introduced quinine as an antimalarial agent, which was distributed to the settlers, including Estonians, and began to drain the land, but the mechanisms of the disease’s origin and spread were unknown. This is also reflected in the disease explanations and treatment methods that were common among Estonian settlers. Folk names and magical healing methods for malaria were brought from Estonia, and were applied in combination with methods from conventional medicine. Neither the first nor the others corresponded to the true nature of the disease. Although malaria has been familiar in Estonia as well, also as a mythological disease, the mythological aspect has not been thoroughly thematized in the material of Caucasian Estonians, which does not mean that it was unknown. Although there are no surviving legends related to malaria as a mythological disease, and malaria is not presented as a disease demon, this may be due to the choice of the medium: our knowledge of Estonians’ struggle with malaria comes from reports sent to Estonian newspapers by the settlers, but the newspapers preferred to publish rational texts – the mythological side of the malaria lore, if it was known, was not present in the articles published in the newspapers. However, some treatment techniques have been preserved that convince that malaria was also explained mythologically. The treatment methods also betray the fact that the line between rational and mythological explanations may have been blurred: both old magical treatment methods and new medications offered by conventional medicine were used. As malaria was one of the main factors hindering settlement activities in the Caucasus, which is reflected by a rather extensive return migration, it acquired an important place in the so-called founding narrative of the settlements over time. Malaria was part of the wild nature that had to be conquered in order to achieve a stable existence and future for ourselves and future generations. The cutting down of dense forests and the struggle with wild animals threatening the settlers’ households was marked by hard work, which in turn testified to the settlers’ work ethic. Malaria was also attributed to intensive work. This confirmed the self-image of Estonians, for whom hard work has an important role. Information about the discovery of the causative plasmodium of malaria at the end of the 19th century, which proved the role of mosquitoes in the spread of malaria, reached the Caucasus with a slight time lag. It especially concerns the late arrival of new knowledge among the colonists – earlier knowledge about the connection of malaria with humidity and poisonous vapours remained among Estonian settlers even in the 20th century. Based on the new knowledge, the authorities improved the previous anti-malaria measures – during the Soviet times, a certain type of fish was cultivated in the water bodies, which destroyed the mosquito larvae. Swamp drainage, anti-humidity measures in building architecture, deforestation for farmlands and eucalyptus planting were in use in the late 19th century and destroyed the breeding grounds for mosquitoes even before the connection between mosquitoes and malaria was discovered. These methods are still in use today, because malaria has not really been eradicated from the Caucasus.